People With COPD Who Respond to Ground-Based Walking Training Are Characterized by Lower Pre-training Exercise Capacity and Better Lung Function and Have Greater Progression in Walking Training Distance. Issue 5 (September 2019) - Ho, Jian Ping; Alison, Jennifer A.; Ng, L. W. Cindy; Wootton, Sally L.; McKeough, Zoe J.; Jenkins, Sue C.; Eastwood, Peter R.; Hillman, David R.; Jenkins, Christine; Spencer, Lissa M.; Cavalheri, Vinicius; Hill, Kylie
Abstract : Purpose: To investigate the characteristics that distinguish responders from nonresponders to ground-based walking training (GBWT) in people with chronic obstructive pulmonary disease (COPD). Methods: An analysis was undertaken of data collected during a trial of GBWT in people with COPD. Responders to GBWT were defined in 2 ways: (1) improved time on the endurance shuttle walk test of ≥190 sec (criterion A); or (2) improved ability to walk, perceived by the participant to be at least "moderate" (criterion B). Differences in participant characteristics, pre-training exercise capacity, health-related quality of life, and the improvement in the distance walked during the training program were examined between responders and nonresponders. Results: Of the 95 participants randomized to GBWT (age 69 ± 8 yr, forced expiratory volume in 1 sec [FEV1 ] % predicted = 43% ± 15%), data were available for analysis on 78 and 73 patients by criterion A and criterion B, respectively. According to criterion A, 32 (41%) participants were responders. The odds of being a responder increased with increasing FEV1 % predicted (OR = 1.2; 95% CI, 1.0-1.5, for every 5% increase) and increased with decreasing pre-training incremental shuttle walk distance (OR = 1.4; 95% CI, 1.0-1.8, for every 50-m decrement). According to criterion B, 42 (58%) participants were responders. There were no differences in characteristics or pre-training measures between the responders and nonresponders. For both criteria, responders demonstrated greater change in the distance walked during the training program ( P < .05). Conclusion: Responders to GBWT had lower pre-training exercise capacity, had better lung function, and demonstrated greater change in the distance walked during the training program. Abstract : Supplemental Digital Content is Available in the Text.This study investigated the characteristics of responders and nonresponders to ground-based walking training (GBWT) in people with chronic obstructive pulmonary disease. Responders to GBWT were characterized by having a lower pre-training exercise capacity and less airflow obstruction and demonstrated greater change in the walking distance during the training program.